Natural compounds from botanical drugs targeting mTOR signaling pathway as promising therapeutics for atherosclerosis: A review - Wu, Qian; Lv, Qianyu; Liu, Xiao’an; Ye, Xuejiao; Cao, Linlin; Wang, Manshi; Li, Junjia; Yang, Yingtian; Li, Lanlan; Wang, Shihan (Frontiers in Pharmacology, 2023)
Atherosclerosis (AS) is a chronic inflammatory disease that is a major cause of cardiovascular diseases (CVDs), including coronary artery disease, hypertension, myocardial infarction, and heart failure. Hence, the mechanisms of AS are still being explored. A growing compendium of evidence supports that the activity of the mechanistic/mammalian target of rapamycin (mTOR) is highly correlated with the risk of AS. The mTOR signaling pathway contributes to AS progression by regulating autophagy, cell senescence, immune response, and lipid metabolism. Various botanical drugs and their functional compounds have been found to exert anti- AS effects by modulating the activity of the mTOR signaling pathway. In this review, we summarize the pathogenesis of AS based on the mTOR signaling pathway from the aspects of immune response, autophagy, cell senescence, and lipid metabolism, and comb the recent advances in natural compounds from botanical drugs to inhibit the mTOR signaling pathway and delay AS development. This review will provide a new perspective on the mechanisms and precision treatments of AS.